Law Schools as Legal Aid Providers in Kenya: Challenges and Lessons Learnt from Practice - Mikinyango, Asha; Nguru, Judith (International Journal Clinical Legal Education, 2021)
Legal aid is the provision of free or subsidized legal services to mainly poor and vulnerable people who cannot afford advocate fees. The right to legal aid is well rooted in the international, regional human rights treaty framework to which Kenya party. The provision of legal aid addresses the concerns of the poor and vulnerable by focusing on challenges that foil access to justice. In recognition of this, the Government of Kenya promulgated the Legal Aid Act, 2016 establishing the National Legal Aid Service to provide legal aid services to needy, marginalized, and vulnerable persons. This was a very important move, propelling the Government to prioritize legal aid provision as a right as well as a necessity for promotion of rule of law and access to justice. However, it is imperative to understand that the duty does not squarely fall on the State alone. There is need for non-state actors' support from private entities like law …
Journal Article
Keywords: Law Schools; Legal Aid Providers; Kenya; Challenges of Legal Practice